A Case Report of Slowly Evolving Epidural Hematoma After Lumbar Drain Removal Following Initiation of Clopidogrel Therapy. Issue 6 (April 2020) - Ranganath, Yatish S.; Arora, Lovkesh; Sondekoppam, Rakesh V.
Abstract : Guidelines on the management of lumbar drain in patients receiving antithrombotic therapy are lacking, with American Society of Regional Anesthesia and Pain Medicine (ASRA) anticoagulation guidelines for regional anesthesia providing the best possible guidance for this scenario. However, the risk–benefits of placing a lumbar drain in the context of vascular surgery differ from placement of neuraxial blockade. One of the changes included in the recently published ASRA guidelines is that clopidogrel can be started on a patient with an indwelling neuraxial catheter. We report a case of slowly evolving epidural hematoma following the initiation of clopidogrel therapy in a patient with an indwelling lumbar drain.